2021
DOI: 10.1093/eurheartj/ehab509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial invasive vs. initial conservative treatment strategies on recurrent and total cardiovascular events in the ISCHEMIA trial

Abstract: Aims The International Study of Comparative Health Effectiveness with Medical and Invasive Approaches (ISCHEMIA) trial prespecified an analysis to determine whether accounting for recurrent cardiovascular events in addition to first events modified understanding of the treatment effects. Methods and results Patients with stable coronary artery disease (CAD) and moderate or severe ischaemia on stress testing were randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Third, the primary endpoint is assessed at 12 months after protocol-mandated complete revascularization; complaints due to myocardial ischemia, which may occur after a period of more than 1 year, will not be recorded. However, data from the ischemia trial appear to suggest that the incidence of angina remains constant during longer follow-up periods ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the primary endpoint is assessed at 12 months after protocol-mandated complete revascularization; complaints due to myocardial ischemia, which may occur after a period of more than 1 year, will not be recorded. However, data from the ischemia trial appear to suggest that the incidence of angina remains constant during longer follow-up periods ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Invasive Approaches -Chronic Kidney Disease (ISCHEMIA-CKD) trials found similar effects in reducing all-cause death or myocardial infarction between initial invasive management compared to initial conservative management, which includes aggressive LDL-C therapies as a standard of care, of patients with chronic coronary disease and moderate to severe ischemia on stress testing without or with advanced CKD [19,20]. Also, a post-hoc analysis of the Aggressive Lipid-Lowering Initiation Abates New Cardiac Events (ALLIANCE) Study demonstrated that in patients with coronary heart disease and CKD, intensive LLT with higher doses of atorvastatin to achieve a target < 80 mg/dL reduced the relative risk of time to the rst cardiovascular event by 28% in patients with CKD (HR, 0.72; 95% CI, 0.54 to 0.97; P = 0.02) and 11% in patients without CKD (HR, 0.89; 95% CI, 0.74 to 1.07; P = 0.3) [21].…”
Section: Recently the International Study Of Comparative Health Effec...mentioning
confidence: 99%
“…In a recent issue of partner journal from the ESC Journals family, the incidence of cardiovascular adverse events at 4 years of follow-up in the ISCHEMIA trial was reported. 1 In such manuscript, authors did not find any significant differences between initial Invasive (INV) or Conservative (CON) strategies in the number of composite or individual cardiac events.…”
mentioning
confidence: 92%
“…However, if we look numbers of cardiovascular death, 3.6% vs. 4.3% with INV and CON strategies, respectively P = 0.176, and all-cause of death 5.6% in both P = 0.944; call to our attention that incidence of non-cardiac death in the INV group would be significant higher compared to the CON ones 2% vs. 1.3%, respectively, P = 0.029 and numbers of non-cardiac death are not reported in the manuscript. 1 Interestingly, most of these were due to cancer accorded to the abstract presentation reported by the same authors in the 2020 American Heart Association meeting. 2…”
mentioning
confidence: 93%
See 1 more Smart Citation